The impact of SARS-CoV-2 infection and vaccination on inflammatory arthritis: a cohort study - Striani, Giovanni; Hoxha, Ariela; Lorenzin, Mariagrazia; Cozzi, Giacomo; Scagnellato, Laura; Vangelista, Tatiana; Frizzera, Francesca; De Sandre, Pierino; Simioni, Paolo; Doria, Andrea; Ramonda, Roberta (Frontiers in Immunology, 2023)
Objectives. To investigate the effects of SARS-CoV-2 infection, as well as short-(within 48 hours) and long-term (within 30 days) adverse events (AEs) of SARS-CoV-2 vaccines, including arthritis flares in a large cohort of patients with inflammatory arthritis (IA).A retrospective cohort study comprising 362 patients: 94 (26%) rheumatoid arthritis, 158 (43.6%) psoriatic arthritis and 110 (30.4%) ankylosing spondylitis; and 165 healthy controls (HC) to ascertain the prevalence and severity of SARS-CoV-2 infection in patients with IA, the rate of AEs associated with SARS-CoV-2 vaccines and disease flares within a month of the vaccination. All patients provided informed consent and data about SARS-CoV-2 infection and/or vaccination status.Results. One-hundred-seventeen (32.3%) patients and 39 (23.6%) HC were affected by SARS-CoV-2 infection. Forty (34.2%) patients experienced an IA flare within one month of infection, of whom 3 (7.5%) needed to switch therapy. The prevalence of SARS-CoV-2 infection, disease severity, and hospitalization rate were not significantly different. At least one shot of SARS-CoV-2 vaccine was administered in 331 (91.4%) patients and 147 (89.1%) HC. Within 48 hours, 102 (30.8%) patients developed vaccine-related AEs; 52 (15.7%) patients with >1 vaccine dose experienced an IA flareup, of whom 12 (23.1%) needed to switch therapy.A significantly higher rate of IA flare was observed among patients who contracted SARS-CoV-2 infection vs. those without infection. Patients with IA experienced flares after SARS-CoV-2 vaccination, though it was not statistically significant.